Evaluation of Signalized Intersection Performance Using Vissim Microsimulation and PKJI 2023 (Case Study: Gunung Sari Intersection In Cirebon City) - Hariani, Mira Lestira; Pradana, Ikhlas Maddinah; Wihardi, Rendy Yogista; Yudiansyah, Yunandhika Agung; Radical, Romeo Yullezia; Al Baihaqi, Fais Hidayah (Journal of Green Science and Technology, 2025)
The development of urban traffic in the city of Cirebon poses challenges to the performance of signalized intersections, particularly at the Gunung Sari intersection, which connects four main corridors: Jl. Cipto Mangunkusumo, Jl. Wahidin, Jl. Tuparev, and Jl. Kartini. This study aims to evaluate the existing performance of the intersection using a manual approach based on the 2023 Indonesian Road Capacity Guidelines (PKJI) and microscopic modeling with PTV VISSIM software. The survey was conducted by recording traffic volume for 5 days between 06:00 and 18:00 WIB, with peak conditions occurring on Saturday between 13:00 and 14:00 WIB at 8,082 vehicles/hour. The traffic composition was dominated by motorcycles (59.54%) and passenger cars (39.03%). The results of the 2023 PKJI analysis showed that all intersection arms in the existing condition were at service level F with an average delay of 92.24–98.24 seconds and a queue length of 76.63–204.84 meters. The 10-year projection shows an increase in the degree of saturation to >1.80 with the highest delay on the Kartini arm of 436.33 seconds. Validation of the VISSIM model using the GEH test produced a value of <5 with a conformity level above 95%, so the model is reliable. The simulation results show that Scenario 1 (simplifying the cycle to 3 phases by combining Wahidin and Cipto) is the most effective alternative because it can reduce the average delay and queue length evenly compared to other scenarios. This study emphasizes the importance of periodic evaluation and the application of simulation-based scenarios in supporting urban traffic management.